Comparing E-learning and Lecture-Based Education in Control of Nosocomial Infections - Mina Sadat Hashemiparast; Roya Sadeghi; Mohammadreza Ghaneapur; Kamal Azam; Azar Tol (Tehran University of Medical Sciences, 2016)
Background and Aim: Effective educational programs, is one of the most basic methods in prevention of Nosocomial infection. This study aimed to compare the effects of E-learning versus lecture-based education in prevention of Nosocomial infections among hospital staffs. Materials and Methods: A randomized pre and posttest control group design was conducted on 98 hospital staffs in 2013 after allocating into two groups of "lecture-based education" and "E-learning". Data were collected by a researcher-made questionnaire which its validity and reliability was confirmed by a pilot study. Wilcoxon, Paired and Independent sample T-test was conducted using SPSS, version18. Results: There was a significant difference for outcomes before and after education based on two approach of lecture-based (p=0.01) and E-learning (p=0.01).The mean and standard deviation of knowledge in lecture-based education and E-learning group were 12.73± 2.76, 11.50 ± 2.64 respectively. The level of knowledge in the lecture group was significantly higher than that of participants in the E-learning group (p=0.02). Conclusion: Despite the effectiveness of E-learning in learning and raising awareness of the learners, using of this method among health-related organizations need to empower employees, remove the barriers and suitable infrastructure.